Extenders with vitamins C and E applied to Rhamdia quelen sperm cryopreservation / Extensores com vitaminas C e E aplicados à criopreservação de esperma de Rhamdia quelen - Xavier, Alan Müller Mendonça (2021)
We performed this experiment to evaluate the effects of adding vitamins C and E on extenders for sperm cryopreservation of Rhamdia quelen over spermatic mobility after thawing. At cryopreservation, sperm samples were diluted in a proportion of 1:3 (v/v), following pre-freezing in nitrogen steam and subsequent immersion in liquid nitrogen. The diluents were composed by 5% milk powder, 5% glucose, 10% methanol and different levels of vitamin. Three sperm cryopreservation tests were carried out with (1) diluent containing 0.0; 4.0; 6.5; 9.0 and 11.5 mg of vitamin C mL-1, (2) diluent containing 0.0; 2.0; 4.0; 6.0 and 8.0 mg of vitamin E mL-1; (3) diluent containing 0.0; 4.0 + 2.0; 6.5 + 4.0; 9.0 + 6.0 and 11.5 + 8.0 mg of vitamin C mL-1 plus vitamin E mL-1, respectively. The spermatic motility rate, spermatic curvilinear velocity, average path and straight line velocities were measured in thawed semen by CASA. Data were submitted to ANOVA and Duncan´s test at 5% of significance. After thawing the effect (P<0.05) of vitamin C was observed only for sperm motility, with higher values (38.2±20.7%) on solution containing 4.0 mg of vitamin C mL-1. The concomitant addition of both vitamins influenced (P<0.05) only the curvilinear velocity, reducing the velocity at any concentration. In conclusion, diluents with 4.0 mg vitamin C mL-1 to cryopreservation of the silver catfish semen improve the sperm quality after thawing, and the use of diluents with vitamin E or both vitamins are not recommended because do not ensure the cells protection.